Design, Synthesis and Characterization of a Phosphino-Azine Ligand - Uxía Barreiro-Sisto; Marcelino Maneiro; Rosa Pedrido (Chemistry Proceedings, 2024)
Azine compounds have recently gained significant attention due to the interesting properties that they display, which could be relevant in fields such as Pharmacology and Material Sciences. These types of ligands stand out in Coordination Chemistry because of the facilities that they exhibit that make it easy to coordinate transition and post-transition metal ions. Furthermore, to the azine skeleton (C=N-N=C), the addition of other donor atoms such as sulfur, oxygen or phosphorus in the ligand increases the coordination possibilities. In this sense, we are interested in azine ligands as precursors of novel metallosupramolecular architectures. The research herein reported is focused on the synthesis and characterization of a potentially tetradentate [P2O2] organic phosphine-azine ligand (LP). The addition of the phosphine group to the azine skeleton allows for the stabilization of soft metal ions and the assembly of functional structures. The azine ligand LP8 has been prepared by a condensation reaction between two equivalents of (diphenylphosphino)benzaldehyde and one equivalent of azine monohydrate, and it was fully characterized by using several techniques such as elemental analysis, mass spectrometry, infrared spectroscopy, 1H NMR spectroscopy and X-ray diffraction.